Association of parental feeding style and screen time with overnutrition among toddlers aged 12–36 months: a case–control study - Nadhiroh, Aim Matun; Wulandari, Putri Setia; Awwalul Wildatil Qodliyah; Mudlikah, Siti (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2026)
Background: Early childhood malnutrition, particularly overnutrition, is an increasing public health concern influenced by behavioral factors such as parental feeding style and children’s screen time. However, studies examining the combined role of these factors among toddlers remain limited. Objective: To analyze the association of parental feeding style and screen time with overnutrition among toddlers aged 12–36 months. Methods: A case–control study was conducted among 66 toddlers, comprising 33 children with overnutrition and 33 with normal nutritional status. Data were collected using structured questionnaires assessing parental feeding style and screen time. Nutritional status was determined using the weight-for-height (W/H) index based on WHO standards. Associations were analyzed using the Chi-square test, and odds ratios (ORs) with 95% confidence intervals were calculated. Statistical significance was set at p<0.05. Results: Democratic feeding style showed a protective association with overnutrition (OR=0.12; p<0.001), whereas permissive feeding style increased the risk (OR=5.81; p=0.021). Authoritarian feeding style showed increased odds but was not statistically significant (p=0.105). Screen time and its duration were significantly associated with overnutrition (p=0.039 and p=0.028, respectively). Negative parental perceptions of screen time were associated with lower odds of overnutrition (OR=0.28; p=0.013). Conclusion: Parental feeding style and screen time are significantly associated with overnutrition among toddlers aged 12–36 months. Interventions should focus on promoting responsive feeding practices and appropriate screen time management to support optimal child growth.